Effect of processing and flavour fine-tuning techniques on the volatile flavour constituents of pseudocereals and some minor cereals - Olaniyi, Lasekan Olusegun; Lasekan, Adeseye O. (WFL Publisher, 2012)
Different processing techniques have been used for many centuries to increase the amount of bioactive components and the subsequent fine-tuning of flavour compounds of pseudocereals and the lesser cereals. After an introduction into the different processing methods that leads to the formation of characteristic flavours in pseudocereal and the lesser cereal products, results of studies aimed at indicating the influence of biotechnical processes (e.g. germination and malting), sourdough/sourslurry fermentation and thermal processing on the final aroma of pseudocereal and the lesser cereal products are summarized in this review. Also, the characteristic flavour compounds in both the native and the products of the pseudocereals and the lesser cereals coupled with their stability are highlighted with respect to their contribution to the overall aroma.